Constructing early childhood leadership models in China: a mixed-methods study. Issue 6 (1st September 2020) - Wang, Mo; Ho, Dora; Lu, Jiafang; Yang, Dongmei
Abstract : Purpose: The purpose of this study is to construct a scale that is contextually suitable for measuring early childhood leadership in China. Design/methodology/approach: Following a standard scale development procedure, both qualitative and quantitative research approaches were addressed. Qualitative data was collected from 21 semistructured interviews with formal and informal teacher leaders in Xiamen City, China. Using survey data of 120 respondents and 305 respondents, an exploratory factor analysis was conducted twice to determine the underlying factorial structure of the scale. A further sample of 317 respondents were used to test the latent structure and validity of the scale using confirmatory factor analysis. Findings: Based on the results from reliability and validity tests, this study indicates that the scale demonstrates sound psychometric properties. A three-factor model was determined, including staff management and development, peer learning and support and communication with parents. Originality/value: The scale is the first of its kind for measuring early childhood leadership in China.